(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the prevalence of PCOS cases among students of the Faculty of Santa Maria, Cajazeiras, Paraíba, analyzing the diagnostic method, therapeutic measures used and the genetic character attributed to the syndrome. The present study was developed according to the design of a descriptive observational cross-sectional quantitative study. We selected 50 academics in a non-probabilistic way. The data were collected through the application of a questionnaire containing ten questions. The analysis of the data revealed a percentage of 24% of those interviewed with the disorder. In addition, the most used diagnostic method in such cases was pelvic ultrasonography, cited by 46.2% of women with PCOS, followed by clinical examination, represented by the changes in the menstrual cycle, which was reported by 30.8% of these participants. All the interviewees with the syndrome reported doing some type of treatment and the most used therapeutic measure was the use of oral contraceptives, followed by the adoption of a healthy lifestyle. None of the women interviewed used insulin-sensitizing drugs. The most common clinical symptom among these women was the alteration of the menstrual cycle, present in 91.6% of them. Proportionately, more women who reported having relatives with PCOS had PCOS. Such data suggest the genetic condition involved in the etiopathogenesis of the same, which can also be influenced by environmental factors.